Does Digital Literacy Empower Adolescent Girls in Low- and Middle-Income Countries: A Systematic Review - Meherali, Salima; Rahim, Komal Abdul; Campbell, Sandra; Lassi, Zohra S. (Frontiers in Public Health, 2021)
Background: The vast majority (90%) of the world's adolescents aged 10–19 live in low- and middle-income countries (LMICs); and in those resource-limited settings, girls face distinct challenges across multiple health, social, and economic domains. Gender equality and girl’s empowerment are key goals in their own right and are central to all other development goals. Digital literacy is a great enabler for the empowerment of young girls. This systematic review aims to identify the range and nature of interventions that have been implemented to empower adolescent girls (10-19 years) through digital literacy in LMICs. Methods: We conducted a systematic review of studies following Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) standards for systematic reviews. Two reviewers selected studies, conducted quality assessments, and extracted data by using standard forms. The collected data include the design of the study, type of digital literacy intervention, target audience, intervention received, intervention reach, data analysis, and study outcomes. The review is registered with PROSPERO (CRD42020216756). Results: Thirty-five studies met the eligibility for inclusion and of those, 11 were experimental studies (randomized controlled trial=6; quasi-experimental=2; before-after with no control=3), 11 were cross-sectional/descriptive studies, seven studies used a mixed-method approach, and six were qualitative studies on digital literacy interventions to empower young girls in LMICs. The majority of digital literacy interventions were designed and implemented to improve sexual and reproductive health rights and decision-making of adolescent girls in LMICs (n=33). Only three papers reported the use of digital media for health-related information and decision making, while only one reported on educational and social empowerment. Discussion: Our findings suggest that digital literacy interventions such as mobile phones, mobile health tools, media exposure, access to the internet, internet-based educational strategies, social media exposure are effective to empower adolescent girls to access health services and information and also enhance the access to educational resources. However, we found inconclusive evidence on the effectiveness of digital literacy to enhance girl's access to financial services and economic empowerment. More rigorous studies with long-term follow-ups to assess the effectiveness of such interventions to empower adolescent girls in LMICs are urgently needed.